2020
DOI: 10.4103/jpbs.jpbs_313_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review of acute, recurrent, and chronic pancreatitis: Recent updates of 2013–2019 literature

Abstract: A BSTRACT The increasing prevalence of pancreatic disorders worldwide has provided challenges in its clinical care and management. This review was aimed to evaluate recent literature on diagnosis, treatment, and management of acute pancreatitis (AP), recurrent acute pancreatitis (RAP), as well as chronic pancreatitis (CP) documented during the past 5–6 years. An extensive literature review was carried out based on studies within the last 6 years (2013–2019). Articles were selected base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although AP is considered a fully reversible disease, it carries a high risk of progressing into recurrent AP or chronic pancreatitis 21 . Gradually, this may lead to type 3c diabetes, pancreatic pseudocyst, or even pancreatic cancer 22–24 . Studies have increasingly reported heightened risk for diabetes or cardiovascular diseases after a single episode of AP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AP is considered a fully reversible disease, it carries a high risk of progressing into recurrent AP or chronic pancreatitis 21 . Gradually, this may lead to type 3c diabetes, pancreatic pseudocyst, or even pancreatic cancer 22–24 . Studies have increasingly reported heightened risk for diabetes or cardiovascular diseases after a single episode of AP.…”
Section: Discussionmentioning
confidence: 99%
“…21 Gradually, this may lead to type 3c diabetes, pancreatic pseudocyst, or even pancreatic cancer. [22][23][24] Studies have increasingly reported heightened risk for diabetes or cardiovascular diseases after a single episode of AP. A systematic review based on 24 prospective studies showed that patients who develop AP have a relative risk of 2.66 (95% CI, 1.86-3.80) for developing diabetes over 5 years.…”
Section: Discussionmentioning
confidence: 99%